Comparative evaluation of quality attributes and shelf life of minimally processed guava vis-a`-vis whole guava (Psidium guajava) fruits during storage - KUMAR, PUSHPA CHETHAN; GARG, NEELIMA; SHUKLA, DHARMENDRA KUMAR; OBEROI, HARINDER SINGH; YADAV, KAUSHLESH (The Indian Journal of Agricultural Sciences, 2017)
Minimally processed guava (Psidium guajava L.) fruits cv. Lalit were compared with whole guava fruits for different quality attributes and shelf life during storage at 10 and 15°C. Whole and minimally processed guavas were analyzed for parameters, like total soluble solids, titratable acidity, ascorbic acid, total polyphenols, lycopene content, polygalacturonase activity and microbial load over a period of 15 days (d). Minimally processed fruits stored at 10°C showed relatively higher concentrations of ascorbic acid, polyphenols and lycopene, compared to whole guava fruits. Sensory evaluation results revealed that minimally processed fruits scored better than the whole guava fruits throughout the storage period, irrespective of the storage conditions. Bacterial load was low in both minimally processed and whole guava fruits stored at 10°C, compared to fruits stored at 15°C. Hence, it can be concluded from this study that minimally processed guava retained quality attributes and bioactive compounds, compared to whole guava fruits during storage at 10°C. Thus, minimally processed guava fruits can serve as suitable alternative to whole guava fruits for consumers’ convenience as well as acceptance.